Study of the Impact of New Rural Cooperatives on the Implementation of the Rural Revitalisation Strategy - Ding, Xiaoyu; Ding, Xiaoxia (Transactions on Economics, Business and Management Research, 2024)
This study aims to explore the impact of new rural cooperatives on the implementation of China's rural revitalisation strategy, focusing on the roles and challenges of new cooperatives in promoting agricultural modernisation, facilitating the optimisation of socio-economic structures, and achieving an ecological civilisation. Through literature review, case study analysis and field research, this study comprehensively assesses the importance and impact of new rural cooperatives in rural revitalisation. The study finds that new rural cooperatives have significantly improved agricultural productivity and product quality and contributed to agricultural modernisation by pooling farmers' efforts and introducing modern agricultural technologies and management models. These cooperatives have also contributed to the optimisation of rural socio-economic structures by providing employment opportunities, skills training and increasing farmers' incomes. In addition, co-operatives have demonstrated a positive role in promoting rural ecological environment protection and sustainable development, such as promoting green agriculture, conserving resources and protecting the ecological environment. At the same time, this study also points out the challenges faced by new rural co-operatives in the process of development, including management and operational efficiency, market adaptability, balance between environmental protection and sustainable development, fund raising and resource allocation. In response to these challenges, the study proposes a series of countermeasures, such as strengthening the internal management of cooperatives, broadening market channels, promoting environmentally friendly agricultural practices, enhancing the effective use of funds and resources, and strengthening policy support and guidance. Overall, new rural cooperatives play an important role in promoting rural revitalisation strategies, and their successful experiences and challenges are of great reference value in guiding the implementation of rural revitalisation strategies. Through an in-depth study of new rural cooperatives, this paper provides practical insights and suggestions for policymakers, cooperative managers and rural development researchers.